Radical oxygen species: an important breakthrough point for botanical drugs to regulate oxidative stress and treat the disorder of glycolipid metabolism - Luo, Maocai; Zheng, Yuhong; Tang, Shiyun; Gu, Linsen; Zhu, Yi; Ying, Rongtao; Liu, Yufei; Ma, Jianli; Guo, Ruixin; Gao, Peiyang; Zhang, Chuantao (Frontiers in Pharmacology, 2023)
Background: The incidence of glycolipid metabolic diseases is extremely high worldwide, which greatly hinders people’s life expectancy and patients’ quality of life. Oxidative stress (OS) aggravates the development of diseases in glycolipid metabolism. Radical Oxygen Species (ROS) is a key factor in the signal transduction of oxidative stress, which can regulate cell apoptosis and contribute to inflammation. Currently, chemotherapies are the main method to treat disorders of glycolipid metabolism, but this can lead to drug resistance and damage to normal organs. Botanical drugs are an important source of new drugs and they are widely found in nature with availability, high practicality, and low cost. There is increasing evidence that herb medicine has definite therapeutic effects on glycolipid metabolic diseases. Objective: This study aims to provide a valuable method for the treatment of glycolipid metabolic diseases with botanical drugs from the perspective of ROS regulation by botanical drugs, and to further promote the development of effective drugs for the clinical treatment of glycolipid metabolic diseases. Methods: Using herb*, plant medicine, Chinese herbal medicine, Phytochemicals, Natural medicine, phytomedicine, Plant extract, botanical drug, ROS, Oxygen free radicals, oxygen radical, oxidizing agent, glucose and lipid metabolism, saccharometabolism, glycometabolism, lipid metabolism, blood glucose, Lipoprotein, triglyceride, Fatty liver, atherosclerosis, obesity, diabetes, dysglycemia, NAFLD, DM as a keyword or subject term, relevant literature was retrieved from Web of Science and PubMed databases from 2017 to 2022, and the relevant literature was summarized. Results: Botanical drugs can regulate ROS by regulating mitochondrial function, endoplasmic reticulum, phosphatidylinositol 3 kinase (PI3K)/protein kinase B(AKT), erythroid 2-related factor 2 (Nrf2), nuclear factor κB (NF-κB) and other signaling pathways to improve oxidative stress and treat glucolipid metabolic diseases. Conclusion: The regulation of ROS by botanical drugs is multi-mechanism and multifaceted. Both cell studies and animal experiments have demonstrated the effectiveness of botanical drugs in the treatment of glycolipid metabolic diseases by regulating ROS. However, studies on safety need to be further improved, and more studies are needed to support the clinical application of botanical drugs.